Three-dimensional structure of the T-layer of Bacillus sphaericus P-1. - Lepault, J (1986)
The three-dimensional structure of the regular surface layer of Bacillus sphaericus P-1 (T-layer) was determined to a resolution of ca. 2.5 nm by electron microscopy and image analysis. The T-layer has P4 symmetry, a lattice constant of 13 +/- 0.2 nm, and a thickness of ca. 8 nm. The reconstruction revealed three distinct domains: a major, a minor, and an arm domain. In the z-direction, the domains are arranged in two planes creating two different surface reliefs.